DEGRADASI EKOLOGI SUMBERDAYA HUTAN DAN LAHAN (Studi Kasus Hutan Rawa Gambut Semenanjung Kampar Propinsi Riau) - -, Rifardi (Bumi Lestari; Vol 8 No 2 (2008), 2012)
The purpose of this study was to clarify relationships between socio-economic activities and forest ecology degradations in Kampar Peninsula, Riau Province, Indonesia. Socio-economic and demographic data were collected from seven districts in three regencies, namely district of Kuala Kampar and Teluk Meranti in Pelalawan Regency, district of Sungai Apit and Dayun in Siak Regency, and district of Merbau, Rangsang and Tebing Tinggi in Bengkalis Regency. All data were collected using Simple Random Sampling and Loting Methods. Results of this study revealed that there were close relationships between socio-economic activities and forest ecology degradations in Kampar Peninsula. The population growth and improvement of socio-economic activities caused land use in Kampar Peninsula forest getting higher. Kampar Peninsula forests were deforested about 260,348 ha (34%) in the period of 1998-2005. The highest deforestation (20%) occurred in the period of 2000-2005. Land use on this forest had increased since 1990 (25,256 ha) and had became increasing in 2005 (162,413 ha).
Keywords: forest degradation, Kampar Peninsula, socio-economic activities.